Results in the Latin America and Caribbean Region - World Bank (Washington, DC, 2014)
A focus on development results is at the heart of the Latin America and Caribbean Region s approach to delivering programs and policy advice with partners in middle-income and low income countries alike. Through knowledge, convening activities, and financial services we strive to help people across the region create better opportunities and build a better future for themselves, their families and their country. Documenting, measuring and evaluating results of what we do, helps us and our partners to engage more effectively, learn from our experiences and apply lessons to the design and implementation of future interventions. This collection of result stories shows our continuous efforts to adopt and integrate technical analysis, timely policy advice, and a variety of financial instruments into programs that are aligned with client priorities. Results show the increased demand and the effectiveness of peer-to-peer learning, have led to a scaling up our support for South-South exchange activities and the use our convening power to support successful partnerships and mobilize additional resources to finance development work.